An investigation of the effect of chlorinated solvents on surface characteristics of S‐65 beryllium. (19th January 2016) - Mallinson, Christopher F.; Kozlowski, Samuel; Harvey, Ann; Watts, John F.
Abstract : Samples of S‐65 beryllium were vapour degreased using six chlorinated solvents and analysed by X‐ray photoelectron spectroscopy. Exposure to the solvent vapour is believed to result in the formation of inorganic chloride at the metal surface, which can act as a corrosion precursor. Exposure to chloroform, tetrachloroethene, pentachlorobenzene and chlorobenzene resulted in the greatest amounts of beryllium chloride formation (>0.8 at.%), while exposure to dichloromethane and 1, 1‐dichloroethene produced the least (<0.5 at.%). Mechanical abrasion of the metal surface while submerged in chloroform resulted in a significant increase in inorganic chloride at the beryllium surface. Rinsing of the samples with distilled water, after exposure to solvent vapours, significantly decreased the amount of organic and inorganic chlorine on the samples but did not result in complete removal of these species. Copyright © 2016 John Wiley & Sons, Ltd.